2007
DOI: 10.1007/s12094-007-0119-z
|View full text |Cite
|
Sign up to set email alerts
|

Can the clinical outcome in state II colon carcinomas be predicted by determination of molecular marker expression?

Abstract: Only Ki-67 and anti-VIII factor were shown to be useful for the prediction of outcome and recurrence rate in curatively treated CC patients. In conjunction with clinical and pathological staging, they may provide a stronger indication of clinical outcome than staging alone and help better select therapeutic options in CC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Our data seem to support the concept of distinct roles for p53 and Bcl-2 in CRC tumorigenesis; while the majority (70%) of carcinomas displayed p53 positivity, the corresponding proportion of positively stained tumors for Bcl-2 was only 46%. This disparity in the observed detection rate is consistent with previous findings (7,9,12,17,20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data seem to support the concept of distinct roles for p53 and Bcl-2 in CRC tumorigenesis; while the majority (70%) of carcinomas displayed p53 positivity, the corresponding proportion of positively stained tumors for Bcl-2 was only 46%. This disparity in the observed detection rate is consistent with previous findings (7,9,12,17,20).…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that such an impact (if any) appears to be staining-dependent (i.e., stronger for tumors with high p53 expression) perhaps explains literature discrepancies on the issue (10,11,14), attributable (in part) to the wide variability in thresholds used to define p53 positivity. Among several studies using different cutoffs and reporting the presence (9,12,18,23) or absence (14,17,20) of a correlation between p53 and stage, only two (17,18) followed the multiple stratification of p53 staining (as we did). Therefore, despite the detected, in that way, significant associations of p53 with either higher stage (18) or poor grade (17), more research is required to determine the clinicopathologically optimal categorization of p53 immunoreactivity.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One possible mechanism by which PGE 2 promotes carcinogenesis is enhancement of cancer cell proliferation. ( 2 ) Previous studies have shown that Ki67 index is correlated with poor prognosis in some types of cancer, ( 38–43 ) although in gastric cancer immunostaining with Ki67 has limited independent value for predicting prognosis, possibly because the prognostic value of Ki67 labeling index in gastric cancer may vary depending on histological type. ( 44 ) Our present study showed that high value of Ki67 labeling index was not associated with an increased probability of gastric cancer–specific mortality in all patients, and in the subgroup of patients with tubular adenocarcinoma Ki67 was associated with cancer‐specific mortality, although it was not independent prognostic factor for poor survival by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of Z. Pap et al showed that in adenoma of the large intestine the Ki-67 expression level directly correlates with seriousness of dysplastic changes [22]. Several studies showed that significant Ki-67 expression is mainly connected to lower overal survival rates [23][24][25][26][27], while other studies highlight that high Ki-67 expression correlates with improvement of general survival and better oncological prognosis [28][29][30].…”
Section: Introductionmentioning
confidence: 99%